Empowering youth and communities through 4-H School Gardening Programs: Results of focus groups in Burundi, Africa - Mary Katherine Deen; Lauren Hrncirik Scanga; Kevin Wright; Charles Berahino (Journal of International Agricultural and Extension Education, 2017)
The quality of education and training children receive today will significantly impact their development into adulthood and their impact on society (Kibwiki & Semana, 2001). Burundi, Africa is the second poorest country in the world and has a turbulent history laced with economic, political, and cultural challenges (Headrick, 2016). With more than half the population under the age of 18, educating the youth of Burundi is paramount to bringing about change in the country. The purpose of this qualitative study was to understand the needs of primary school teachers, administrators, afterschool program educators and their students; and to determine if a 4-H Youth Development school gardening program was a viable methodology to meet their needs. The desire of local partners to empower Burundian youth and the fact that empowerment is a fundamental principle of the 4-H methodology led to the selection of Empowerment Theory as the conceptual framework for this study. A needs assessment using focus groups was conducted with 34 primary school teachers, administrators, and afterschool staff in two rural communities in Burundi. Findings indicated that poverty and hunger were the primary barriers to quality education and climbing out of poverty. School educators also reported a need for professional development to better provide quality education for youth. Based on the outcomes of the focus groups, the researchers recommend that the 4-H Youth Development school gardening program is implemented in rural Burundi using Empowerment Theory as a framework to address the needs of educators and youth.
Keywords: Needs assessment; Burundi; Educators; School Gardens; 4-H Youth Development; Empowerment Theory